Analisis Model Jejaring Kebijakan dalam Pengelolaan Kebijakan Berbasis Kolaborasi antar Instansi Pemerintah Provinsi Jawatengah - Rizky Ilhami (Lembaga Pengembangan Kinerja Dosen, 2025)
Public policy management in the context of modern governance requires effective collaboration between government agencies. One relevant approach to addressing this complexity is the policy network model. This study aims to analyze the policy network model in collaboration-based policy management between government agencies in Central Java Province. This study uses a qualitative approach with a descriptive-analytical method. Data were obtained through documentation studies, policy analysis, and reviews of coordination and collaboration practices between government agencies. The results show that the policy network that has been formed is still partial and not yet systematically integrated. The main problems identified include fragmentation of authority, weak inter-agency coordination, sectoral ego, limited data integration, and low capacity of human resources in managing policy collaboration. This study concludes that strengthening the policy network model through collaborative leadership, institutionalizing inter-agency cooperation, integrating information systems, and increasing the capacity of the apparatus are key to realizing effective, adaptive, and sustainable public policy management.